Biocompatibility of Mesoporous Silica Nanoparticles?. Issue 2 (3rd March 2016) - Shi, Yi; Miller, Michael L.; Di Pasqua, Anthony J.
Abstract : Mesoporous silica nanoparticles (MSNs) have been widely explored as drug delivery vehicles in cell and animal studies. To move this nanoparticle platform into the clinic, however, further work needs to be done to predict and assess potential adverse reactions and side-effects to optimize for their efficacious and safe use in patients. Toxicity may be dependent on a number of characteristics, including the size, shape, surface chemistry, and charge of MSNs. Thus, altering various physical and chemical properties of MSNs, while controlling for others, should reveal important parameters necessary for biocompatibility. In this work, reports on biocompatibility of MSNs in recent years have been reviewed and the effects of size, shape, surface chemistry, and porosity highlighted. Advances in triggered release of the drug from MSN delivery systems are also discussed. This article brings together current research on MSN biocompatibility and emphasizes the need for standardized characterization of MSNs, predictive cell studies, and harmonization of animal studies by investigators in the field, to move these sophisticated nanodevices from bench to bedside. GRAPHICAL ABSTRACT: